2006
DOI: 10.1590/s1517-83822006000400024
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A in wines and grape juices commercialized in the city of São Paulo, Brazil

Abstract: During the summer of 2005, a total of 101 samples of wines and grape juices purchased from supermarkets and retail stores in São Paulo city were analysed for the presence of Ochratoxin A (OTA). OTA was evaluated in 29 red wines and 38 grape juices produced in Brazil and in 34 imported red wines (from Argentina, Chile, Uruguay, France, Italy, Portugal, Spain and South Africa). OTA was extracted in an immunoaffinity column and detected by HPLC with fluorescence detection, according to EN 14133/2003. The detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
(25 reference statements)
4
19
0
2
Order By: Relevance
“…OTA levels in juices were lower than 2ng mL -1 in other studies cited in table 1, in which the occurrence of this mycotoxin was evaluated, including samples from Brazil (ROSA et al, 2004;SHUNDO et al, 2006), China (CAO et al, 2013, Spain (BELLI et al, 2004), Malaysia (LEE et al, 2012 and Switzerland (ZIMMERLI & DICK, 1996). In these cases, the OTA exposure through consumption of juice has not represented a health risk, since the estimated exposure to this toxin were lower than the value established as PTWI by JECFA (ZIMMERLI & DICK, 1996;ROSA et al, 2004;BELLI et al, 2004;SHUNDO et al, 2006;LEE et al, 2012;CAO et al, 2013).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…OTA levels in juices were lower than 2ng mL -1 in other studies cited in table 1, in which the occurrence of this mycotoxin was evaluated, including samples from Brazil (ROSA et al, 2004;SHUNDO et al, 2006), China (CAO et al, 2013, Spain (BELLI et al, 2004), Malaysia (LEE et al, 2012 and Switzerland (ZIMMERLI & DICK, 1996). In these cases, the OTA exposure through consumption of juice has not represented a health risk, since the estimated exposure to this toxin were lower than the value established as PTWI by JECFA (ZIMMERLI & DICK, 1996;ROSA et al, 2004;BELLI et al, 2004;SHUNDO et al, 2006;LEE et al, 2012;CAO et al, 2013).…”
Section: Introductionmentioning
confidence: 78%
“…Since OTA was first detected in these beverages sold in Switzerland (ZIMMERLI & DICK, 1996), several studies about the occurrence of OTA are found in the literature (Table 1 and 2). The concentration of OTA in juice and wine is often reported below of legislation limit (2ng mL -1 ) (WOESE, 2000;NG et al, 2004;ROSA et al, 2004;SHUNDO et al, 2006;QUINTELA et al, 2012;CAO et al, 2013;LASRAM et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The studies about the occurrence of OTA in Brazilian juices are incipient. Literature data are mainly related to juice produced by enzymatic method (also called as Welch) (ZIMERLI E DICK, 1996;ROSA et al, 2004;SHUNDO et al, 2006;LEE et al, 2012;CAO et al, 2013).…”
Section: Palavras-chave: Micotoxina Compostos Tóxicos Ochratoxin Amentioning
confidence: 99%
“…The levels found in 91% of samples marketed in Malasia were of 0.02 to 1.05μg L -1 (LEE et al, 2012). In evaluations of juice produced in Brazil, no sample presented OTA levels above the maximum limit established by Brazilian legislation (2μg L -1 ) (ROSA et al, 2004;SHUNDO et al, 2006). ROSA et al (2004) analyzed 64 grape juice samples marketed in Rio de Janeiro city, Brazil.…”
Section: Palavras-chave: Micotoxina Compostos Tóxicos Ochratoxin Amentioning
confidence: 99%
See 1 more Smart Citation